(untitled) (Altre Modernità, 2023)
This study is concerned with placing Italian graphic novelist Zuzu in the international current of graphic novelists (Spiegelman, Sacco, and Satrapi) who, by means of their autobiographical graphic novels, present personal experiences imbued with political value, following the concept of ’the personal is political’ coined by feminist Carol Hanisch. Giulia Spagnulo, aka Zuzu, shows us the image of a dystopian body in her first published graphic novel, Cheese (2019). Here, the protagonist Zuzu, suffering from bulimia, accomplishes her journey of recovery from the eating disorder thanks mainly to the bond of solidarity established with her friends. In the second published work, Happy Days (2021), the author instead represents the image of an utopian body. Through continuous reference to Samuel Beckett’s play Happy Days, the author tells the story of Claudia and her attempt to assume an utopian body, monstrous and capable of committing violence, which overcomes emotional dependence, gains self-love and achieves self-acceptance. Both protagonists succeed in their goal of realising a ’utopian action’, namely the attempt to bring about a positive change in their lives in relation to a malaise generated by an inner and personal problem, an aspect that marks the most important difference with the works of Spiegelman, Sacco, and Satrapi.